D-REAMS: A New Compact AMS System for Radiocarbon Measurements at the Weizmann Institute of Science, Rehovot, Israel. Issue 3 (23rd December 2016) - Regev, Lior; Steier, Peter; Shachar, Yigal; Mintz, Eugenia; Wild, Eva Maria; Kutschera, Walter; Boaretto, Elisabetta
Abstract: The Dangoor REsearch Accelerator Mass Spectrometer (D-REAMS) is a dedicated carbon-only AMS system, built by National Electrostatics Corporation (NEC). It is based on the 1.5SDH Pelletron, operating at 460 keV. The machine was installed at the Weizmann Institute of Science, Rehovot, Israel, in January–February 2013, and passed the acceptance test on March 2013. Since then, over 4500 samples have been successfully measured. Here, we present the results of an intercomparison experiment, done in collaboration with the Vienna Environmental Research Accelerator (VERA), and some typical operation parameters and measurement values of the new AMS system.